Analysis of accelerations in turbulence based on generalized statistics - Arimitsu, T.; Arimitsu, N. (Condensed Matter Physics, 2003)
An analytical expression of probability density function (PDF) of accelerations in turbulence is derived with the help of the statistics based on generalized entropy (the Tsallis entropy or the Ren´ yi entropy). It is revealed that the derived PDF explains the one obtained by Bodenschatz et al. in the measurement of fluid particle accelerations in fully developed turbulence at Rλ = 970 .